The problem of alternative financing source management: The equity crowdfunding case - Anna Motylska-Kuźma (e-Finanse: Financial Internet Quarterly, 2019)
The main objective of this paper is to analyze one of the alternative sources of financing - equity crowdfunding - from the point of view of managerial processes. Based on the case study analysis and the comparative analysis the problems and challenges of raising funds using equity crowdfunding are discussed, comparing the findings with the issuing of shares. The analysis show that although many of the activities undertaken in raising funds through issuing shares and equity crowdfunding are similar, the managerial processes in the case of equity crowdfunding require from the company first of all building and caring about relationships with investors, rather than showing and proving effectiveness. In exchange for the low legal requirements, the equity crowdfunding investors expect good communication even if the promises are not fulfilled.
Keywords: G24; G30; G32; 330; managerial processes; equity crowdfunding; alternative finance